2018
DOI: 10.1038/s41598-018-27587-8
|View full text |Cite
|
Sign up to set email alerts
|

Low-affinity Nerve Growth Factor Receptor (CD271) Heterogeneous Expression in Adult and Fetal Mesenchymal Stromal Cells

Abstract: Human multipotent mesenchymal stromal cells (MSC) are isolated from a plethora of tissue sources for cell therapy purposes. In 2006, the International Society for Cellular Therapy (ISCT) published minimal guidelines to define MSC identity. Nevertheless, many independent studies demonstrated that cells meeting the ISCT criteria possessed heterogeneous phenotypes and functionalities, heavily influenced by culture conditions. In this study, human MSC derived from many adult (bone marrow and adipose tissue) or fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 53 publications
4
62
0
1
Order By: Relevance
“…To investigate a clinically relevant age-associated effect on skeletal stem cell frequency and function, we first examined iliac crest bone graft (ICBG) samples from 36 patients (20 male, 16 female) with ages ranging from 24 to 89 y who underwent operative fixation of an upper-or lower-extremity fracture. FACS with CD271 as a human skeletal stem cell marker (8)(9)(10)(11) revealed that SSPC frequency significantly declined with increasing age ( Fig. 1 A and B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate a clinically relevant age-associated effect on skeletal stem cell frequency and function, we first examined iliac crest bone graft (ICBG) samples from 36 patients (20 male, 16 female) with ages ranging from 24 to 89 y who underwent operative fixation of an upper-or lower-extremity fracture. FACS with CD271 as a human skeletal stem cell marker (8)(9)(10)(11) revealed that SSPC frequency significantly declined with increasing age ( Fig. 1 A and B).…”
Section: Resultsmentioning
confidence: 99%
“…FACS analysis was performed by using a BD LSRII cell analyzer with high-throughput sampler. CD45-negative and CD271-positive SSPCs were displayed as percentages of total single cell number (8)(9)(10)(11). Patient data, including radiographic and clinical time to union, were extracted from a prospective patient database at the NYU Langone Orthopedic Hospital.…”
Section: Methodsmentioning
confidence: 99%
“…There is a belief that the minimal criteria set out by the Mesenchymal and Tissue Stem Cell Committee of the International Society for Cellular Therapy are no longer a robust enough method of determining MSC authenticity [30], as they could be used to characterise fibroblastic cell strains [31]. Moreover, there are reports in the literature supporting a theory that transplanted MSCs themselves do not differentiate to form new tissue in vivo, but rather migrate to a site of injury or disease and secrete factors which stimulate the resident stem cells to construct new tissue [32].…”
Section: Differentiationmentioning
confidence: 99%
“…Concerning the capacity for differentiation, multiple studies carried out have made it possible to perceive that MSCs are capable not only of traditional tridifferentiation but also of originating other cells and tissues with mesodermal (ligaments, tendons, cardiomyocytes, muscles), ectodermal and endodermal origin (skin, retina, lungs, hepatocytes, renal tubes, pancreatic islets, sebaceous glands and ducts and neural cells) [12]. Also, recently new markers have been explored to identify those that can be considered stemness-associated MSC stromal cell markers, in opposition to the traditional MSC markers that some authors question and indicate as more appropriate to be considered stromal cell markers [13]. In this group, CD271 is indicated as a potential precursor for homogeneous subpopulations of MSCs and described as a way to improve culture homogeneity.…”
Section: Introductionmentioning
confidence: 99%